1990
DOI: 10.1093/nar/18.17.5197
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of well-defined phosphate-methylated DNA fragments: the application of potassium carbonate in methanol as deprotecting reagent

Abstract: A new deprotection procedure in the synthesis of (partially) phosphate-methylated oligodeoxynucleotides has been developed, involving treatment of fully protected DNA fragments with methanolic potassium carbonate. It is shown that base deprotection can be accomplished in potassium carbonate/methanol without affecting the methyl phosphotriesters. This methodology enables us to synthesize, both in solution and on a solid support, DNA fragments which are phosphate-methylated at defined positions. The solid phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 19 publications
(13 reference statements)
0
31
0
Order By: Relevance
“…For the deprotection of the Fmoc-protected amino bases three hours were included. Model experiments demonstrated approximately 5% demethylation [17]. The 31P NMR data of the phosphatemethylated DNA 18-mer at 2.0 ppm showed one single broad resonance spectrum, due to the complexity of the diastereomeric mixture.…”
Section: H Nmr Spectroscopy Of Phosphatemethylated 18-mer D(cactcaccmentioning
confidence: 95%
“…For the deprotection of the Fmoc-protected amino bases three hours were included. Model experiments demonstrated approximately 5% demethylation [17]. The 31P NMR data of the phosphatemethylated DNA 18-mer at 2.0 ppm showed one single broad resonance spectrum, due to the complexity of the diastereomeric mixture.…”
Section: H Nmr Spectroscopy Of Phosphatemethylated 18-mer D(cactcaccmentioning
confidence: 95%
“…[12][13][14] It should be mentioned that a number of research groups have tried to synthesize long fragments of phosphatemethylated DNA involving solid supports. This procedure was used by Kuijpers et al for the synthesis of welldefined phosphatemethylated DNA fragment, [20] and by Alul et al for the synthesis of sensitive oligonucleotide derivatives. [21] Before demethylation, according to the normal procedure, the phosphatemethylated DNA was removed from the support with K 2 CO 3 /CH 3 OH or dilute NH 3 -H 2 O/CH 3 OH, respectively.…”
Section: Phosphatemethylated Dnamentioning
confidence: 99%
“…Most of this work is laid in a great number of US patents (1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011). In the background of their inventions, they mention that incorporation of the methylphosphotriester linkages following the method of Kuijpers et al [20] has its limitation as a consequence of considerable demethylation, whereas the method of Alul et al was carried out (only) with thymine. [21] The procedure as described by Moody et al and Buck et al was canceled based on the retracted Science paper of 1990 as mentioned before, vide supra.…”
Section: Phosphatemethylated Dnamentioning
confidence: 99%
“…Detection of the imino proton in the NMR analysis demonstrated that the second silylation did not occur at the oxygen atom at the C2 or C4 positions. The benzoyl group of 4 was removed with potassium carbonate in methanol, [17] and the 3'-hydroxyl function of 5 was phosphitylated with (2-cyanoethyl)-N,N-diisopropylchlorophosphoramidite. [18] Using the building block 6 and the tBPA-protected phosphoramidites of the other nucleosides, a 6-mer, d(GCTgAGC), a 13-mer, d(ACGCGATgACGCCA), and a 30-mer, d(CTCGTCAGCATCTTgCATCATACAGT-CAGTG), were synthesized on a solid support (Tg represents thymine glycol).…”
Section: Synthesis Of Thymine Glycol Containingmentioning
confidence: 99%